Pengaruh Variasi Produk Terhadap Minat Beli Konsumen Erigo Store Melalui Media Instagram - Ian Ricky Prasitya (Transformasi: Journal of Economics and Business Management, 2023)
This research wants to find out more about "The Effect of Product Variation on Consumer Purchase Interest" in accordance with the subject matter raised, namely the Effect of Product Variation on Consumer Purchase Interest at Erigo Store through Instagram Media. The background to this research is that in the current digital era, social media, especially Instagram, has become a popular platform for e-commerce businesses to promote and sell their products. In this context, this study tries to understand how the variety of products offered by erigo stores through the media of their Instagram accounts affect consumer buying interest. The purpose of this study was to find out how product variations in Erigo store products can influence consumer buying interest, to find out what factors most influence consumers in choosing Erigo store products through Instagram media. The method used in this research is descriptive quantitative research method based on positivistic (concrete data), research data in the form of numbers that will be measured using statistics as a means of calculating the test, related to the problem under study to produce a conclusion. The population in this study are followers of Instagram Erigo store. Conclusions based on the results of the analysis and discussion of money that the researchers have explained, it can be concluded that attractive and varied product variations can increase consumer buying interest.